Barriers to the implementation of plan initiative (P4K) in Badung District - Putri Mariani; Putu Widarini; Alex Pangkahila (Universitas Udayana, 2013)
The family-centered safe birthing initiative (P4K) is aimed to reduce maternal and newborn mortality rates. The P4K program involves the distribution of promotional stickers by community health care workers. In 2011, the coverage of the P4K had reached 100% of villages, and 98.9% of expectant mothers had attached the promotional sticker on a visible section of their homes. However, the process is reported not implemented using standard procedures before placing the sticker on their homes. This study is aimed to explore the barriers to the implementation of P4K in Badung. This study was descriptive qualitative using phenomenology approach. Data were collected using focus group discussion (FGD) with 20 midwives and 10 cadres, in-depth interviews (with 6 expectant mothers and 3 husbands/family members) and participant observation of P4K implementation in public health centers. Secondary data was obtained through relevant P4K document analysis. Informants were purposively selected using the criteria of 1) midwives already trained in P4K, 2) cadres already trained in P4K and 3) P4K participating expectant mothers. Research findings indicate that knowledge, attitude and mother’s and husband’s behaviour impact negatively upon program implementation. There is also an evidence of lack of logistical support including: P4K administrational forms, IEC pamphlets and transportation costs. Midwives and participating healthcare providers have a very good knowledge; however, their behaviour does not demonstrate this. The poor governance of centres and high mobility of expectant mothers also impacted upon program implementation. Future recommendations include program widening of scope and upscale, increased logistical support, continual monitoring and evaluation, research into program funding governance as well as upscale involvement of stakeholders.